(untitled) (Kronika Bydgoska, 2020)
The Bydgoszcz Dram a School was one of the art education institutions in Bydgoszcz. It operated in 1945-1948. The school founder and its first director was Aleksander Rodziewicz. The institution was also managed by Adam Grzymała-Siedlecki. The school graduates included Wanda Rucińska and Hieronim Konieczka. The school, despite enthusiasm and active work, experienced constant financial problems, which led to its closing.